2010
DOI: 10.1603/ec09334
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Relative Humidity and Product Moisture on Response of Diapausing and Nondiapausing Indianmeal Moth (Lepidoptera: Pyralidae) Larvae to Low Pressure Treatments

Abstract: Low pressure treatment in flexible polyvinyl chloride containers is a potential alternative to chemical fumigants for California tree nuts. Laboratory studies investigated the effect of relative humidity and product moisture on weight loss and mortality of diapausing and nondiapausing larvae of the Indianmeal moth, Plodia interpunctella (Hübner) (Lepidoptera: Pyralidae), exposed to 50 mmHg. Diapausing larvae were far more tolerant than nondiapausing larvae to low pressure; exposure times nearly twice those of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Adults and larvae may later be present in the final packaged products (Riudavets et al, 2009;Noomhorm et al, 2009). Although stored product insects are relatively more susceptible to the MA treatments, their eggs are relatively tolerant to the high CO2 environment (Adler, 1999;Adler et al, 2000;Johnson, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adults and larvae may later be present in the final packaged products (Riudavets et al, 2009;Noomhorm et al, 2009). Although stored product insects are relatively more susceptible to the MA treatments, their eggs are relatively tolerant to the high CO2 environment (Adler, 1999;Adler et al, 2000;Johnson, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, low pressure may also be used in combination with high CO2 in the containers or packages. Johnson & Zettler (2009) and Johnson (2010) showed that vacuum treatment could be effectively used to control storage pests of tree nuts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The egg is typically the most tolerant life stage (Mbata and Phillips 2001). Lowering the humidity during low pressure treatment can enhance insect mortality (Johnson 2010). Effective low pressure treatments can be several hours or several days in duration depending on the level of pressure and other factors (Johnson and Zettler 2003, Liu 2003, Mbata and Phillips 2004.…”
Section: Discussionmentioning
confidence: 99%
“…Published research into the use of low pressure for disinfestation of stored products infested by stored-product pests dates back to Ͼ85 yr (Back and Cotton 1925, Bare 1948, Calderon et al 1966, Calderon and Navarro 1968, Navarro and Calderon 1979, Friedlander and Navarro 1983, Mbata and Phillips 2001, Johnson and Zettler 2009, Johnson 2010. Low oxygen concentrations cause the insect mortality rather than any physical effect of the low pressure or dehydration resulting from low moisture Calderon 1979, Friedlander andNavarro 1983).…”
mentioning
confidence: 99%